April lady - Heyer, Georgette (Naperville, Ill. : Sourcebooks Casablanca, 2011)
When young newlywed Lady Nell Cardross begins to fill her days with fashion and frivolity, the earl has to wonder whether she really did marry him for his money, as his family so helpfully suggests. And now Nell doesn't dare tell him the truth ...
"Originally published in Great Britain in 1957 by William Heinemann"--T.p. verso.
Keywords: Man-woman relationships; Love stories; Regency fiction; Historical fiction; Love stories; Regency fiction; Historical fiction